Ethical values and green purchase intentions: Mediating effects of egobiocentric values and green behavior - Sonko, Mariama; Arslan, Mahmut (International Journal of Management and Sustainability, 2026)
The study aims to integrate the theory of planned behavior and the Hunt-Vitell ethical theory to evaluate consumers’ sustainable consumption behaviors and intentions in a least developed nation. Conducting a PLS-SEM analysis with a sample size of 300 Gambians, the findings revealed that deontological and teleological evaluations have positive and significant direct effects on consumers’ green product purchase intentions. However, the magnitude of the impact was higher with teleological evaluations than with deontological evaluations. Furthermore, the relationships between deontological evaluations, teleological evaluations, and green product purchase intention were found to be partially mediated by egobiocentric values. Similarly, green purchase behavior also partially mediated the relationship between green product purchase intention and green product repurchase intention. Additionally, results from the multi-group analysis indicate that green price sensitivity does not significantly moderate the relationship between green product purchase intention and green purchase behavior. Based on the findings, the study suggests recommendations relevant to green businesses and policymakers. First, to capture the attention of green-oriented consumers, marketing managers should focus on the green features of their products to persuade consumers. Also, favorable policies from the government should be enacted to promote the competitiveness and operations of green businesses in this region.